Boundary Conditions for Expectancy Theory Predictions of Work Motivation and Job Performance - Kopelman, Richard E.; Thompson, Paul H. (Academy of Management Journal, 1976)
Expectancy theory predictions of work motivation and job performance are examined. As hypothesized, predictions were materially strengthened by taking into account the effects of five boundary conditions: (a) time, (b) initial level of the criterion, (c) level of rewards, (d) task-specific ability, and (e) organizational control system responsiveness.